2018
DOI: 10.1371/journal.pone.0199777
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the circadian clock and TGF-β signaling pathway in zebrafish

Abstract: BackgroundTGF-β signaling is a cellular pathway that functions in most cells and has been shown to play a role in multiple processes, such as the immune response, cell differentiation and proliferation. Recent evidence suggests a possible interaction between TGF-β signaling and the molecular circadian oscillator. The current study aims to characterize this interaction in the zebrafish at the molecular and behavioral levels, taking advantage of the early development of a functional circadian clock and the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…Previous research suggests that Alantolactone indirectly activates Smad2/3 signalling downstream of Activin by making ActR-II more bioavailable [17]. A recent study in zebrafish demonstrated that Alantolactone activated TGFβ signalling in a concentration-dependent manner to subsequently cause disruption of the circadian clock [25]. This is in line with our observations of similar Activin-and Alantolactone-induced increases in pSMAD2/3 levels and a dose-dependent effect of Alantolactone on efficiency of MSN differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research suggests that Alantolactone indirectly activates Smad2/3 signalling downstream of Activin by making ActR-II more bioavailable [17]. A recent study in zebrafish demonstrated that Alantolactone activated TGFβ signalling in a concentration-dependent manner to subsequently cause disruption of the circadian clock [25]. This is in line with our observations of similar Activin-and Alantolactone-induced increases in pSMAD2/3 levels and a dose-dependent effect of Alantolactone on efficiency of MSN differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…After translation, Per2 and Cry1a proteins dimerize and translocate to the nucleus where they interact directly with the CLOCK: BMAL heterodimer, thereby inhibiting its transcriptional activation including the transcription of Per2 and Cry1a (Frøland Steindal & Whitmore, 2019). This cycle takes about 24 h and drives dependent circadian processes in cells by regulating the expression of transcription factors that then control numerous target genes (Li et al, 2013;Sloin et al, 2018;Ramasamy et al, 2019). It should be noted that due to duplication events that occurred during teleost evolution (Liu et al, 2015), the zebrafish genome contains several homologs of known clock genes, among which Per2 and Cry1a act as components of the core clock mechanism (Ziv et al, 2005;Tamai, Young & Whitmore, 2007;Vatine et al, 2009); Cry2a and Cry2b are induced by both the CLOCK:BMAL complex and also by light; while Cry1b, Per1a, Per1b, and Per3 are induced by the CLOCK:BMAL complex but not by light (Hirayama et al, 2019).…”
Section: Circadian Oscillators In Zebrafishmentioning
confidence: 99%
“…Unique MF GO-terms included various signaling pathways and receptor activity such as Wnt/Frizzled binding (dRGC1), epinephrine binding (mRGC1), collagen binding (vRGC1), retinoic acid binding (vRGC2), chromatin binding (NB), insulin binding (NE), and glutamate receptor binding (GIs+) (Figure 3G, Dataset S1H). Many of these signaling pathways were shown to be required for normal functioning and plasticity of the zebrafish brain (Bhattarai et al, 2016b; Diotel et al, 2013; Jiao et al, 2011; Shimizu et al, 2018; Sloin et al, 2018; Tallafuss et al, 2015; Than-Trong et al, 2018); however, their specific involvement for certain subtypes of NSPCs was not shown before. Therefore, our results provide a detailed resource on specific molecular regulatory networks, constitute a starting point for underlying the heterogeneity of the NSPC populations, and serves as a comprehensive repository for researchers interested in certain molecular programs.…”
Section: Resultsmentioning
confidence: 99%